2023
DOI: 10.2147/jaa.s433515
|View full text |Cite
|
Sign up to set email alerts
|

Dupilumab Treatment Efficacy and Impact on Clinical Scores, Serum Biomarkers, and Itch in Adult Patients with Atopic Dermatitis: A Retrospective Analysis

Mariateresa Rossi,
Luca Bettolini,
Grazia Artelli
et al.

Abstract: Purpose Dupilumab, a fully human monoclonal antibody that inhibits the signaling pathways of interleukin (IL)-4 and IL-13, has demonstrated remarkable efficacy in the treatment of atopic dermatitis (AD). Dupilumab has been reported to attenuate itch and reduce several serum markers, including blood lactate dehydrogenase (LDH), blood eosinophil count, and serum total immunoglobulin E (IgE). Patients and Methods The present study investigated retrospectively changes in cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Approximately 80% of AD patients have been reported to have elevated serum IgE levels. 29 The results of this study showed that repeated acupoint injections of AWB, autologous total IgG, or heterologous total IgG effectively reduced the severity of the symptoms and skin thickening, indicating the beneficial effects of these treatments on AD. Furthermore, TB staining revealed a significant decrease in mast cell infiltration in all treatment groups, suggesting a positive effect of these methods in suppressing mast cell accumulation in AD mice.…”
Section: Discussionmentioning
confidence: 59%
“…Approximately 80% of AD patients have been reported to have elevated serum IgE levels. 29 The results of this study showed that repeated acupoint injections of AWB, autologous total IgG, or heterologous total IgG effectively reduced the severity of the symptoms and skin thickening, indicating the beneficial effects of these treatments on AD. Furthermore, TB staining revealed a significant decrease in mast cell infiltration in all treatment groups, suggesting a positive effect of these methods in suppressing mast cell accumulation in AD mice.…”
Section: Discussionmentioning
confidence: 59%